Análise e interpretação do primeiro canto de Os Lusíadas - PANTOJA, Dorotéia Ferreira (2021)
This article aims to read and explain the first song of the Portuguese epic of Camões, Os Lusíadas with the production of an analysis and interpretation of the division of singing in line with parallels of themes with the contemporary. To this end, we use bibliographic support on the historical context and based on the concepts of poetic theory, such as the Poetics of Aristotle and Anazildo Silva Vasconcellos in History of the Brazilian Epic (2007) and the base text of the poem by Virgílio C. Dias (2005). ) with the thesis that Portugal exists by its own will, the core by which the poem can be understood and by the wonderful and historical plan that form the model of epic poetry.